"Kiedy wypełnią się dni..." Analiza egzegetyczno-teologiczna 2 Sm 7, 12; Jr 23, 5; Iz 11, 3-4 - Szwarc, Urszula (The Biblical Annals, 2017)
The contents of the article is a discussion of the verses II Sam 7, 12; Jer 23, 5; Isa 11,3-4 that aims at sketching the picture of reality called "the fullness of the time", which appears from them. It allows saying that it will come along with the appearance in the world of somebody who will seem to be marked by some kind of kinship with Jesse and David. He will be a king whose kingdom will be made lasting (II Sam 7, 12); his rule will consist in fulfilling the law and realising justice (Jer 23, 5). The sign of this will be, on the one hand, respect for and defence of the weak, poor and humiliated, and on the other, inflicting just punishment on the guilty ones (Isa 11, 3-4).